2019
DOI: 10.1242/dev.173161
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of mouse and human sinoatrial node cells reveals a conserved genetic program

Abstract: The rate of contraction of the heart relies on proper development and function of the sinoatrial node, which consists of a small heterogeneous cell population, including Tbx3 + pacemaker cells. Here, we have isolated and characterized the Tbx3 + cells from Tbx3 +/Venus knock-in mice. We studied electrophysiological parameters during development and found that Venus-labeled cells are genuine Tbx3 + pacemaker cells. We analyzed the transcriptomes of late fetal FACS-purified Tbx3 + sinoatrial nodal cells and Nppb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 89 publications
(123 reference statements)
8
48
1
3
Order By: Relevance
“…2D,E, Fig. S4E), as reported previously (Liang et al, 2015;Puskaric et al, 2010;van Eif et al, 2019;Wiese et al, 2009). Thus, C0 and C1 correspond to the SAN cells.…”
Section: Scrna-seq Reveals Distinct Gene Expression Profiles Underlyisupporting
confidence: 85%
See 2 more Smart Citations
“…2D,E, Fig. S4E), as reported previously (Liang et al, 2015;Puskaric et al, 2010;van Eif et al, 2019;Wiese et al, 2009). Thus, C0 and C1 correspond to the SAN cells.…”
Section: Scrna-seq Reveals Distinct Gene Expression Profiles Underlyisupporting
confidence: 85%
“…We performed exo utero ECG on wild-type embryos from embryonic day 12.5 (E12.5) to E16.5 and found that the P waves, which accurately reflect atrial depolarization, became detectable at E12.5, and appeared typically from E13.5 onwards ( Fig. S2), consistent with a previous report that SAN cells begin to exhibit typical action potential (AP) configurations of pacemaking activity at E12.5 (van Eif et al, 2019). Therefore, we isolated the SAN and adjacent atrial tissues from E13.5 Nkx2.5 Cre/+ ;Shox2 HA-DsRed ;R26R YFP embryos.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, as the newly formed chambers differentiate and acquire a secondary, or “working”, myocardial phenotype, the OFT myocardium retains its primary myocardial phenotype. While the properties of the working myocardium are associated with high expression of genes involved in respiratory-chain function, myofibril assembly, fast impulse conduction, and the contractile apparatus, primary myocardium marks nodal cells of the pacemaker and conduction system [ 38 ]. During fetal development, the RVOT differentiates into a more working myocardium phenotype, indicated by loss of expression of Tbx2 [ 39 ].…”
Section: The Right Ventricular Outflow Tractmentioning
confidence: 99%
“…We investigated the role of transcriptional regulators (transcription factors) and post-transcriptional regulators (microRNAs) in defining the level of HCN4. HCN4 mRNA levels are regulated by the transcription factors AP1 39 , Isl1 40,41 , Mef2c 39 , Nkx2.5 42 , NRSF 43 , Tbx3 44 and Tbx18 45 ; BMP2, BMP4 and Shox2 are sinus node specific transcription factors 46 . For example, the transcription factors, Tbx3 and Tbx18, are known to control the pacemaking phenotype of the sinus node and ectopic expression of Tbx3 and Tbx18 in working myocardium causes an upregulation of HCN4 and a switch to a sinus node phenotype 44,45 .…”
Section: Resultsmentioning
confidence: 99%